Cost of vaccine delivery strategies in low- and middle-income countries during the COVID-19 pandemic. Issue 35 (16th August 2021) - Banks, Christina; Portnoy, Allison; Moi, Flavia; Boonstoppel, Laura; Brenzel, Logan; Resch, Stephen C.
Abstract: Background: The COVID-19 pandemic has disrupted immunization services critical to the prevention of vaccine-preventable diseases in many low- and middle- income countries around the world. These services will need to be modified in order to minimize COVID-19 transmission and ensure the safety of health workers and the community. Additional budget will be required to implement these modifications that ensure safe delivery. Methods: Using a simple modeling analysis, we estimated the additional resource requirements associated with modifications to supplementary immunization activities (campaigns) and routine immunization services via fixed sites and outreach in 2020 US dollars. We considered the following four categories of costs: (1) personal protective equipment (PPE) & infection prevention and control (IPC) measures for immunization sessions; (2) physical distancing and screening during immunization sessions; (3) delivery strategy changes, such as changes in session sizes and frequency; and (4) other operational cost increases, including additional social mobilization, training, and hazard pay to compensate health workers. Results: We found that implementing a range of measures to protect health workers and communities from COVID-19 transmission could result in a per-facility start-up cost of 466–799 for routine fixed-site delivery and 12–220 for routine outreach delivery, and 12–108 per immunization campaign site. A recurrent monthly cost of 137–1, 024 for fixed-site delivery and 152–848 for outreach delivery per facility could be incurred, and a 0.32–0.85 increase in the cost per dose during campaigns. Conclusions: By illustrating potential cost implications of providing immunization services through a range of strategies in a safe manner, these estimates can provide a benchmark for program managers and policy makers on the additional budget required. These findings can help country practitioners and global development partners planning the continuation of immunization services in the context of COVID-19.